Sie sind auf Seite 1von 15

Discrete Systems Design And Analysis

Towards A New Framework


Mohammad Al Jamal
December 2018

Abstract
In these notes we introduce a new framework for discrete systems
design and analysis. This new framework is, in some sense, dual to that
of the Z transform, with some notable advantages, including simplicity.

Introduction
The standard mathematical toolkit for the design and analysis of linear discrete
systems has been the Z transform. However powerful this tool is, it has its
mathematical and practical limitations. In these notes, we highlight some of
these limitations, and propose a new mathematical framework, that relies heav-
ily on the more powerful Laplace transform, and some subtle relations between
generating functions of different types. As an application of this new frame-
work, we propose a new discretization technique, that maintains the frequency
response of the system we wish to discitize almost intact after discretization.

Mathematical Background
Suppose that g(y) is an entire function, so that it has the everywhere convergent
Taylor expansion :

X yn
g(y) = an
n=0
n!

Now, for the real parameter τ , define the function fτ (t) :


∞ ∞ ∞ ∞
def
X tm X tm X (mτ )n X φn (t)
fτ (t) = g(mτ ) = an = et an τ n
m=0
m! m=0 m! n=0 n! n=0
n!

Where φn (·) are the single variable Bell polynomials, also known as Touchard
polynomials, and are given by :
 n ∞ n  
d X mn tm X n k
φn (t) = e−t t et = e−t = t
dt m! k
m=0 k=0

1
 
n
Where are the Stirling numbers of the second kind. These polynomials
k
have the generating function :

x
−1)
X φn (t) n
et(e = x
n=0
n!

For a fixed value of τ , the function g(mτ ) is a discrete version of the continuous
function g(t), where it’s periodically sampled at a fixed frequency of f = τ −1 .
By convention, it is written as g(mτ ) = g[m].
The function fτ (t) is related to g(t)-or more accurately, to its Laplace transform-
by :
Z σ+i∞
1
fτ (t) = exp (teτ s ) Ls {g(t)} ds (1)
2πi σ−i∞
Where σ lies to the right of the largest real part of the singularities of Ls {g(t)}.
This can be shown by expanding the exponential, and then applying the Bromwich
inversion formula. In many interesting cases, the integral above may be com-
puted easily using the residue theorem.
Using the fact that :
m!
Lz {tm } = n+1
z
We also have :

X
Lz {fτ (t)} = g[m]z −m−1 = z −1 Zτ {g[m]}
m=0

Where Zτ {g[m]} is the unilateral Z transform of g[m], and the Laplace transform
on the LHS is taken w.r.t. the complex parameter z.
Taking the Laplace transform of eq.(1) w.r.t. the complex parameter z, we
obtain : Z σ+i∞
1 Ls {g(t)}
z −1 Zτ {g[m]} = ds
2πi σ−i∞ z − esτ
Thus :
σ+i∞
Ls {g(t)}
Z
1
Zτ {g[m]} = ds (2)
2πi σ−i∞ 1 − z −1 esτ
Which in most interesting cases can be computed easily using the residue theo-
rem. This is the first instance of duality between the functions g[m] and fτ (t).
The formulae above are superior to the original definition of the Z transform,
since they enable us to compute the Z transform for a wider range of sequences.
For example, consider the sequence g[m] = m!. The infinite sum :

X m!
Z1 {m!} =
m=0
zm

converges nowhere, and thus, the Z transform of g[m] = m! is not defined.


However, we may assign a finite value to this sum using the fact that :
∞ ∞
X m! m X 1
f1 (t) = t = tm = |t| < 1
m=0
m! m=0
1−t

2
By analytic continuation, f1 (t) can be extended to the whole positive real line,
except for t = 1, where there is a first order pole. Taking the Laplace transform
of f1 (t) w.r.t. z, we have :
Z ∞ −tz  Z y −tz Z ∞ −tz
e e e
Lz {f1 (t)} = PV dt = lim dt+ lim dt = e−z Ei(z)
0 1 − t y→1 −
0 1 − t y→1 +
y 1 − t

where Ei(·) is the exponential integral function, and PV stands for Cauchy’s
principal value of the improper integral. Thus :

Z1 {m!} = ze−z Ei(z)

Curiously, the asymptotic expansion for the expression above for a sufficiently
large |z| is given by :
 
−z 1 2! 3! k!
ze Ei(z) = 1 + + 2 + 3 + ... + O
z z z zk

which -formally- coincides with the original, non-convergent definition of the Z


transform of g[m] = m!.
A closely related duality that we wish to explore is the unique mapping between
linear difference equations whose solution is g[m] and linear differential equa-
tions whose solution is fτ (t). Consider the nth order ordinary linear differential
equation :

dfτ (t) d2 fτ (t) dn fτ (t)


α0 (t)fτ (t) + α1 (t) + α2 (t) 2
+ ... + αn (t) = βτ (t)
dt dt dtn
Using the definition of fτ (t), we have :

dk fτ (t) X tm
= g[m + k]
dtk m=0
m!

Substituting the derivatives in each corresponding term in the differential equa-


tion above we obtain:

X tm
(α0 (t)g[m] + α1 (t)g[m + 1] + α2 (t)g[m + 2] + ... + αn (t)g[m + n]) = βτ (t)
m=0
m!

We consider the following three cases :

1-Homogeneous difference equations with constant coefficients

In this case, we have :

dfτ (t) d2 fτ (t) dn fτ (t)


a0 fτ (t) + a1 + a2 + ... + an =0
dt dt2 dtn
which may be rewritten as :

X tm
(a0 g[m] + a1 g[m + 1] + a2 g[m + 2] + ... + an g[m + n]) =0
m=0
m!

3
which holds iff the following difference equation holds :

a0 g[m] + a1 g[m + 1] + a2 g[m + 2] + ... + an g[m + n] = 0

In order to solve for g[m], we solve the corresponding differential equation, and
differentiate fτ (t) m times at t = 0 to obtain:

g[m] = fτ(m) (0)

Going the other way around, from the difference equation to the corresponding
differential equation is trivial. As a first example, consider the linear difference
equation :

g[m + 3] − 7g[m + 2] + 8g[m + 1] + 16g[m] = 0 (g[0] = 1, g[1] = −2, g[2] = 3)

The corresponding differential equation is :


d3 fτ (t) d2 fτ (t) dfτ (t)  0 00

3
−7 +8 +16fτ (t) = 0 fτ (0) = 1, fτ (0) = −2, fτ (0) = 3
dt dt2 dt
The characteristic polynomial of this ODE is :

x3 − 7x2 + 8x + 16 = (x + 1)(x − 4)2 = 0

Hence, fτ (t) has the solution :

fτ (t) = c1 e−t + c2 e4t + c3 te4t

Using the initial conditions, we obtain the solution :


7 −t 2 4t
fτ (t) = e − e + te4t
5 5
Using the series expansion of the exponential function, we obtain :
7 2
g[m] = fτ(m) (0) = (−1)m − 4m + m4m−1
5 5
As a second example, consider the linear difference equation :

g[m + 2] − 4g[m + 1] + 13g[m] = 0 (g[0] = 2, g[1] = 1)

The corresponding differential equation is :


d2 f1 (t) df1 (t)  0

2
−4 + 13f1 (t) = 0 f1 (0) = 2, f1 (0) = 1
dt dt
The characteristic polynomial of this ODE is :

x2 − 4x + 13 = (x − 2 + 3i)(x − 2 − 3i) = 0

Hence, fτ (t) has the solution :

f1 (t) = c1 e(2+3i)t + c2 e(2−3i)t = e2t c1 e3it + c2 e−3it




Using the initial conditions, we obtain :


   
i (2+3i)t i (2−3i)t
f1 (t) = 1 + e + 1− e
2 2

4
Using the series expansion of the exponential function, we obtain :
   
(m) i m i m
g[m] = fτ (0) = 1 + (2 + 3i) + 1 − (2 − 3i)
2 2
After some simplification, we obtain :

g[m] = 5 13m/2 cos(mφ + ψ)
Where :
3 1
φ = tan−1 ψ = tan−1
2 2

2-Inhomogeneous difference equations with constant coefficients

In this case, we have :


dfτ (t) d2 fτ (t) dn fτ (t)
a0 fτ (t) + a1 + a2 + ... + an = βτ (t)
dt dt2 dtn
which may be rewritten as :

X tm
(a0 g[m] + a1 g[m + 1] + a2 g[m + 2] + ... + an g[m + n]) = βτ (t)
m=0
m!

which holds iff the following difference equation holds :


def
a0 g[m] + a1 g[m + 1] + a2 g[m + 2] + ... + an g[m + n] = βτ(m) (0)) = b[m]
As before, in order to solve for g[m], we solve the corresponding differential
equation, and differentiate fτ (t) m times at t = 0 to obtain:
g[m] = fτ(m) (0)
Going the other way around, from the difference equation to the corresponding
differential equation is a little bit harder than the first case. Consider the
inhomogeneous linear difference equation with constant coefficients:
a0 g[m] + a1 g[m + 1] + a2 g[m + 2] + ... + an g[m + n] = b[m]
We can transform this difference equation into a corresponding differential equa-
tion by computing :

X tm
βτ (t) = b[m]
m=0
m!
Or Z σ+i∞
1
βτ (t) = exp (teτ s ) Ls {b(t)} ds
2πi σ−i∞
when the Laplace transform of b(t) is well defined, and when the integral above
converges. And then we solve for fτ (t) in :
dfτ (t) d2 fτ (t) dn fτ (t)
a0 fτ (t) + a1 + a2 2
+ ... + an = βτ (t)
dt dt dtn

5
And as before :
g[m] = fτ(m) (0)
As an example, consider the inhomogeneous linear difference equation :

g[m + 2] − g[m + 1] = ψ(m + 1) (g[0] = 1, g[1] = −2)

Where ψ (·) is the digamma function. We proceed by computing β1 (t):



X tn
β1 (t) = ψ(m + 1) = et (log t + Γ(0, t))
m=0
n!

Where Γ(·, ·) is the incomplete gamma function. The corresponding differential


equation reads :

d2 f1 (t) df1 (t) 0


− = et (log t + Γ(0, t)) (f1 (0) = 1, f1 (0) = −2)
dt2 dt
Solving the differential equation by the method of series expansion, we obtain :

f1 (t) = c1 et + c2 + Ei(t) − tet + (t − 1)et log t − log t + (t − 1)et Γ(0, t)

Using the initial conditions, we obtain :

f1 (t) = 2(1 − γ) − (1 + t)et + [Ei(t) − log t] + (t − 1)et [Γ(0, t) + log t]

Where γ is the Euler-Mascheroni constant. Using the series expansions :



X tk
Ei(t) − log t = γ +
kk!
k=1

and :

X (−t)k
Γ(0, t) + log t = −γ −
kk!
k=1

We obtain :
(m) 1
g[m] = f1 (0) = −m − 2 + + (m − 1)ψ(m + 1) m>1
m
Where we used :
m
X 1
γ + ψ(1 + m) =
k
k=1

3-Inhomogeneous difference equations with variable coefficients

In this case, we have the difference equation :


n
X
αj [m]g[m + j] = b[m]
j=0

6
Multiplying both sides with tm /m! and taking the summation over m = 0, 1, 2, ...
we obtain :

n X ∞
X tm X tm def
αj [m]g[m + j] = b[m] = βτ (t)
j=0 m=0
m! m=0 m!

Taking the Laplace transform of both sides w.r.t. the complex parameter z, we
obtain :
Xn X ∞
αj [m]g[m + j]z −m = zLz {βτ (t)}
j=0 m=0

The inner-most summation is a Hadamard product of the two series :



X
aj [m]z −m = zLz {Aj,τ (t)}
m=0

and :

dj
X  
−m
g[m + j]z = zLz fτ (t) (0 6 j 6 n)
m=0
dtj
Where we define :

def
X tm
Aj,τ (t) = aj [m]
m=0
m!
Using Hadamard’s formula for his product of series, we have :
n
dj
I X  
1 dν
L νz {Aj,τ (t)} Lν fτ (t) = Lz {βτ (t)}
2πi Γ j=0 dtj ν

Where Γ is a positively oriented path in the complex plane, enclosing the ori-
gin, but none of the singularities of the integrand. Taking the inverse Laplace
transform of both sides w.r.t. the complex parameter z, we obtain :
n
dj
I X  
1
Aj,τ (νt)Lν f τ (t) dν = βτ (t)
2πi Γ j=0 dtj

Now, we decompose the function βτ (t) into n linearly independent functions


βj,τ (t), such that :
I  j 
1 d
Aj,τ (νt)Lν fτ (t) dν = βj,τ (t)
2πi Γ dtj

By Nachbin’s theorem, we have :

1 ∞
 j  Z
d x
Lν j
f τ (t) = βj,τ A−1
j,τ (x)dx
dt ν 0 ν

Where A−1
j,τ (x) is uniquely determined by the integral equation :
Z ∞ x u
A−1
j,τ (x)Aj,τ dx =
0 u u−1

7
Now, using the multiplication theorem of the Laplace transform, and choosing
a set of functions ηj (ν) that have inverse Laplace transforms, such that :
Z ∞ Z c+i∞ Z ∞
1 ηj (ν − σ) x
βj,τ A−1
j,τ (x)dσdx = βj,τ (x)e−νx dx
2πi 0 c−i∞ σ σ 0

and defining the new variable σy = x in the left hand side, such that :
Z ∞ Z c+i∞ Z ∞
1 −1
ηj (ν − σ)βj,τ (y) Aj,τ (σy)dσdy = βj,τ (x)e−νx dx
2πi 0 c−i∞ 0

we obtain the condition :


Z c+i∞
1
ηj (ν − σ)A−1
j,τ (σx)dσ = e
−νx
2πi c−i∞

Multiplying both sides with Aj,τ (x), and taking the integration with respect to
x over the positive real line, we obtain :
Z c+i∞
1 ηj (ν − σ)
dσ = Lν {Aj,τ (x)}
2πi c−i∞ σ−1
Taking the inverse Laplace transform of both sides, and defining :

Θj (t) = L−1
t {ηj (ν)}

we obtain :
c+i∞
eσt
Z
Θj (t)
dσ = Θj (t)et = Aj,τ (t)
2πi c−i∞ σ−1
From which we finally obtain:
 
n j
X d
 Aj,τ (t) j  fτ (t) = et βτ (t)
j=0
dt

We solve this inhomogeneous differential equation with variable coefficients for


fτ (t). And as before, the solution of the corresponding difference equation is
given by :
g[m] = fτ(m) (0)

Reconstruction of g(t)
Now, we use the integral representation of the gamma function to obtain :
Z ∞
Γ(a + 1)
ta e−st dt = <(s) > 0
0 sa+1
Thus :
∞ n
dn Γ(a + 1)
Z
n −st 1X
(log t) e dt = n = bk (log s)k
0 da sa+1 a=0 s
k=0

8
Therefore, there exist nth order polynomials in log t, that we’ll denote by Φ†n (t),
such that :
Z ∞
(log s)n
Φ†n (t)e−st dt =
0 s
Now, without loss of generality, we put s = ez , and we obtain :
Z ∞
z
e−t Φ†n (t)e−t(e −1) dt = z n e−z
0

Or equivalently :
Z ∞ ∞
X φm (−t) m
e−t Φ†n (t) z dt = z n e−z (n = 2, 3, 4...)
0 m=0
m!

Integrating by parts, and using the generating function of φn (−t), we obtain :


∞ ∞
dΦ†n (t) X φm (−t) m
Z
e−t z dt = z n
0 dt m=0 m!

Comparing the two sides, we obtain the biorthogonality condition :


Z ∞
dֆ (t)
e−t n φm (−t)dt = m!δnm (3)
0 dt

From which we obtain :



dֆn (t)
Z
an τ n = fτ (−t) dt n = 1, 2, 3...
0 dt

When the integral converges. Alternatively, we integrate (3) by parts, and use
the fact that φn (0) = 0 n = 1, 2, 3..., and we obtain :
Z ∞ h i
0
e−t Φ†n (t) φm (−t) + φm (−t) dt = m!δnm (4)
0

From which we obtain :


Z ∞
0
an τ = n
fτ (−t)Φ†n (t)dt n = 1, 2, 3...
0

When the integral converges. In many cases, the function fτ (t) is not easy to
find in closed form, and the integrals of the individual terms in their current
form don’t converge, thus we employ the trick :
∞ ∞
X tl X tm
g(lτ ) = et g ? (mτ )
l! m=0
m!
l=0

Where, by the binomial transform :


m  
?
X m
g (mτ ) = (−1)m−k g(kτ )
k
k=0

9
Hence :
∞ Z ∞
X (−1)m ? dΦ† (t)
an τ =n
g (mτ ) e−t tm n dt
m=0
m! 0 dt
Now, we use the Stirling transform to obtain :
m  
m
X mk
t = (−1) φ (−t)
k k
k=1
 
m
Where are the absolute Stirling numbers of the first kind. Using (3), we
k
obtain :   
n m
Z ∞ †
dΦ (t) 
(−1) n! , n 6 m
e−t tm n dt = n
0 dt
0 , n>m

Thus :
∞ ∞
(−1)m−n m ?
 
an n X X s(m, n) ?
τ = g (m) = g (mτ )
n! m! n m!
m=n m=n

Were s(·, ·) are the signed Stirling numbers of the first kind. Using the integral
representation of the signed Stirling numbers of the first kind :
I
m!
s(m, n) = z −m−1 logn (z + 1)dz
2πin! |z|=1

and the fact that s(m, n) = 0, n > m, we obtain :


∞ I
an n 1 X
τ = g ? (mτ )z −m−1 logn (z + 1)dz (5)
n! 2πin! m=0 |z|=1

By the binomial transform, we have :



X
? −m z
g (mτ )z = Zτ {g[m]}
m=0
1+z z→ 1
1+z

Using eq.(5), we obtain :



tn
I  
X 1 1 t
g(t) = an = Zτ {g[m]} (z + 1) τ −1 dz
n=0
n! 2πi |z|=1 z+1

It should be noted that the formula above is valid when the ROC of Zτ {g[m]}
is contained in the unit disk. To enlarge the domain of validity of the formula
above, we notice that the function (z + 1)−1 maps the unit circle to the vertical
line <(z) = 21 . Thus, taking (z + 1)−1 → z, we obtain :
1
2 +i∞
Z
1 t
g(t) = − Zτ {g[m]} (z) z − τ −1 dz (6)
2πi 1
2 −i∞

Depending on where the poles of Zτ {g[m]} (z) are, we close the contour to the
right or the left, and use the residue theorem to compute g(t).

10
Some properties of Φ†n (x)
We use :
n
dn dn

(log s) 1 Γ(1 + z)
= (−1)n n s−z−1 = (−1)n n

s dz z=0 dz Γ(1 + z) sz+1 z=0
n Z ∞ Z ∞ n
xz

n d 1 z −sx n d −sx

= (−1) x e dx = (−1) e dx
dz n Γ(1 + z) 0 z=0 0 dz n Γ(1 + z)
z=0
n z
d x
which is a Laplace transform of (−1)n dz n Γ(1+z) evaluated at z = 0. Thus, by

inverse Laplace transform we have :


n
xz

† n d

Φn (x) = (−1)
dz n Γ(1 + z) z=0

Which implies that the polynomials Φ†n (x) have the generating function :

xz X (−z)n
= Φ†n (x)
Γ(1 + z) n=0 n!

Differentiating both sides w.r.t. x, and using the formula zΓ(z) = Γ(1 + z), we
obtain the recurrence formula :
dֆn+1 (x)
x + (n + 1)Φ†n (x) = 0
dx
Using the generating function of Φ† (x), we have :

x−z X (−z)n
= Φ†n (x−1 )
Γ(1 + z) n=0 n!

Dividing both sides by Γ(1 − z), we have :


∞ ∞
x−z 1 X (−z)n 1 X zn
= Φ†n (x−1 ) = Φ†n (x)
Γ(1 + z)Γ(1 − z) Γ(1 − z) n=0 n! Γ(1 + z) n=0 n!

Thus :
∞ ∞
X (−z)n Γ(1 − z) X † −1  z n
Φ†n (x) = Φ x
n=0
n! Γ(1 + z) n=0 n n!
Thus :
n
αk Φ†k (x−1 )
X
Φ†n (x) =
k=0
0
The biorthogonality of φn (−x) and Φn† (x) implies the completeness relation :

X dΦ†n (x) φn (−x0 )
e−x0 = δ(x − x0 ) x>0
n=1
dx n!

δ(·) being the Dirac delta function. Using the recurrence formula for the
Touchard polynomials :
h 0
i
φn+1 (x) = x φn (x) + φn (x)

11
and for consistency of notation, defining :
φn+1 (−x)
Φn (x) = −
xn!
we may rewrite (4) as :
Z ∞
e−x Φn (x)Φ†m (x)dx = δnm
0

The completeness relation can be written as :



X
e−x0 Φ†n (x0 )Φn (x) = δ(x − x0 ) x>0
n=0

It remains to say that Φ†n (x) could be written explicitly as :


n
X ak+1 n−k
Φ†n (x) = (−1) n! n
(log x)
(n − k)!
k=0

Where ak are the Taylor coefficients occurring in the expansion of the reciprocal
gamma function.

Applications in discrete systems


The application of the various discretization methods to time-continuous sys-
tems almost always results in loss, or deformation, of some of the properties of
the original systems, while other properties are maintained intact, or as close
as possible to those of the original time-continuous systems. In this section,
we propose a new discretization method, where the frequency response of the
original time-continuous system is maintained as close as possible to that of the
original time-continuous system we wish to discretize .
Consider the transfer function H(s) of a time-continuous, time-invariant sys-
tem. We want to discretize this system, such that we obtain a new transfer
function in the Z domain, that has the same frequency properties of the original
system H(s). We proved that - under certain conditions - every Z transform of
a certain sequence, is a z multiple of a Laplace transform of a time continuous
function evaluated at z. Thus, if we want to maintain the frequency response
of our system after dicretization, we must have :
Z ∞


gτ (t)e−te dt

H(s) = Zτ {ĝ[m]} =e (7)
z=esτ 0

Where gτ (t) and ĝ[m] are unknown, and as before, are related to each other by:

X tm
gτ (t) = ĝ[m]
m=0
m!

Equation (7) can be written as :


Z ∞

Ls {h(t − τ )u(t − τ )} = e−t gτ (t)e−t(e −1)
dt
0

12
Where h(t) is the impulse response function of our time-continuous system we
wish to discretize, and u(t) is the Heaviside step function. Or, using the gener-
ating function of the Touchard polynomials:
Z ∞ ∞
−t
X φn (−t)
Ls {h(t − τ )u(t − τ )} = e gτ (t) (sτ )n dt
0 n=0
n!

Assuming that H(s) doesn’t have a pole at the origin, we have :


Z ∞
dn
[Ls {h(t − τ )u(t − τ )}]s=0 = τ n
e−t gτ (t)φn (−t)dt
dsn 0

Assuming that gτ (t) has the expansion :


∞ ∞
X gm dֆm (t) 1 X ֆ (t)
gτ (t) = =− gm+1 m
m=1
m! dt t m=0 m!

and using the biorthogonality condition we obtained earlier, we have :


dn
[L∫ {h(t − τ )u(t − τ )}]s=0 = τ n gn
dsn
Using the theorem :

dn
Z
[Ls {f (t)}]s=0+ = lim+ (−p)n f (p)e−sp dp
dsn s→0 0

We have :
Z ∞  p n+1
gn+1 = lim − h(p − τ )u(p − τ )e−sp dp
s→0+ 0 τ
Inserting this expression in the expansion of gτ (t), and using the generating
function of Φ† (t), we obtain :
Z ∞ p −1
tτ −sp
gτ (t) = lim+ p h(p − τ )u(p − τ )e dp

s→0 0 Γ τ

Using the fact that the reciprocal gamma function decays faster than any ex-
ponential function, the limit may be taken before the evaluation of the integral,
and the above formula can be written as :
Z ∞ p −1

gτ (t) =  h(p − τ )u(p − τ )dp (8)
0 Γ τp

To obtain Zτ {ĝ[m]}, we take the Laplace transform of both sides w.r.t. the
complex parameter z, and use the standard result :
Z ∞
tb−1 e−zt dt = Γ(b)z −b
0

and we obtain :
Z ∞ Z ∞
− τp p
Zτ {ĝ[m]} = z z h(p − τ )u(p − τ )dp = z e− τ log z
h(p − τ )u(p − τ )dp
0 0

13
   
− log z log z log z
= ze H = Zτ {ĝ[m]} = H
τ τ
As expected! This result is of no practical use, except if we take the first
approximation of log z, in which case we obtain the bilinear transform. What
we wish to do is to obtain an accurate approximation of Zτ {ĝ[m]} in a different
way.
We assume that gτ (t) can be written in terms of Laguerre polynomials as :

X
gτ (t) = gn ln (t)
n=0

Where :
n  
−t/2
X n (−1)k
ln (t) = e Ln (t) Ln (t) = tk
k k!
k=0

and :
∞ ∞ ∞ p
t τ −1
Z Z Z
gn = gτ (t)ln (t)dt = lim+  h(p − τ )u(p − τ )ln (t)e−sp dtdp
0 s→0 0 0 Γ τp

Using the fact that :


∞ n  
n (−2)k 
Z
−t/2 p X p p p
p p
e t τ −1 Ln (t)dt = 2 τΓ k+ = 2τ Γ Jn
0 k k! τ τ τ
k=0

where the polynomials Jn (x), are given by :


n n   k
X an,j an,j X n 2
Jn (x) = xj = (−1)j s(k, j)
j=0
j! j! k k!
k=j

we obtain :
Z ∞ p
p
gn = lim+ 2 τ e−sp Jn h(p − τ )u(p − τ )dp
s→0 0 τ
Z ∞
= lim 2τ e−ux Jn (x + 1) h(τ x)dx
u→− log 2 0
We use : ∞  n
2z − 1
Z
−tz 2
e ln (t)dt =
0 2z + 1 2z + 1
And we obtain :
∞  n
2z X 2z − 1
Zτ {ĝ[m]} = gn
2z + 1 n=0 2z + 1

We use the partial fraction decomposition:


n n  
n (−1)k

2z − 1 X
=
2z + 1 k z+1 k

k=0 2

14
FIR filter design
The formula we obtained in the last section is very suitable for the design of time-
discrete FIR filters, whose frequency response mimic that of time-continuous
filters with frequency response H(iω). For instance, consider the very simple
filter :
1
H(s) =
s+a
The impulse response function of this filter is given by :

h(t) = e−at

Applying eq.(9) to this filter, and terminating the M deformation of the z trans-
form at M = 3, with sampling period τ = 0.005 gives a very good approximation
of the time-continuous filter.

References
[1]H.Bateman, Tables Of Integral Transforms
[2]H.Bateman, Higher Transcendental Functions
[3]H.A. Priestley, Introduction to Complex Analysis
[4]N.Luhmann, Introduction To Systems Theory

15

Das könnte Ihnen auch gefallen